Literacy Level of Students in Chemistry Education Department on Thermochemistry - Ika Farida Yuliana; Rendy Priyasmika; Fatayah Fatayah (Proceeding of International Conference on Islamic Education, 2021)
This study aims to identify the chemical literacy level of students on Physical Chemistry course, especially in Thermochemisty. Chemical literacy is a major goal in chemistry education recently. The measuring of chemical literacy level in this study used a chemical literacy instrument developed based on Shwartz, et.al framework. The instrument measure students' chemical literacy skills at each level. There are 4 levels of literacy that are measured, namely nominal literacy (level 1), functional literacy (level 2), structural literacy (level 3) and multi-dimensional literacy (level 4). The objects in this study were 14 first year students of Billfath University who took Physical Chemistry course. The data were collected after student got the Thermochemistry subject. The measurement results show that 14.29% of students reach level 3, 71.42% of students reach level 2 and 14.29% of students reach level 1. These results indicate that there is no student that able to reach the highest level 4. Overall, the chemical literacy level of first year students in the Physical Chemistry course is classified as low level. These results allow further development in learning to increase students' chemical literacy level.